A Three-dimensional Measurement Method for High-speed Train Body Based on Binocular Structural Light - ZHANG Haiyang; CHEN Wei; YE Songtao; CHEN Xinyu (Kongzhi Yu Xinxi Jishu)
Putty sanding quality of high-speed train body-in-white has a great influence on wind resistance of train. Sanding quality is mainly judged by the measurement of surface smoothness. Currently, manual detection method is widely used, which has the disadvantages of low quality and low efficiency. Binocular-based measurement method, which has the advantages of high efficiency and high-precision, has gradually been paid more attention to the measurement of large-sized workpieces. It proposed a binocular-based measurement method for high-speed train body-in-white, expanded phases based on the multi-frequency heterodyne expansion algorithm and established a "polar slope-phase" search container for fast matching. Finally, a high-speed white-body measurement experiment was carried out to verify the binocular structured light precision and speed performance of this method.